Comparison of two methods for evaluating lower urinary tract symptoms in cervical cancer patients following radical hysterectomy - Fang An; Sha Wang; Zhiqi Wang; Lingying Wu; Qiubo Lv; Aiming Lv; Hongwu Wen; Jinsong Han; Yumei Wu; Yunong Gao; Qing Liu; Sumei Wang; et al. (BMJ Publishing Group, 2021)
Objective: To compare the degree of agreement and consistency of urodynamic studies (UDS) with low urinary tract symptoms (LUTS) questionnaires for evaluating LUTS in cervical cancer patients following radical hysterectomy (RH) and pelvic lymphadenectomy. Methods: From January 2012 to March 2015, 204 cervical cancer patients who underwent RH in 13 hospitals were evaluated using the Incontinence Questionnaire-Female Lower Urinary Tract Symptoms (ICIQ-FLUTS) and the Overactive Bladder Symptom Score (OABSS). Urodynamic tests were also performed on these patients during the same period. Results: Study participants' age ranged from 23 to 75 years, with a mean (standard deviation) of 48.0 ​± ​9.3 years. Using questionnaires, the prevalence of patients with LUTS symptoms, including storage symptoms, voiding symptoms, stress urinary incontinence (SUI) and overactive bladder (OAB) was 86.3%, 77.0%, 62.7%, 52.9% and 14.7%, respectively. For UDS, the corresponding prevalence was 89.7%, 70.1%, 66.7%, 46.6% and 13.2%, respectively. The diagnostic concordance of questionnaires and UDS for storage symptoms, voiding symptoms, SUI and OAB was 79.9%, 66.7%, 66.7%, 57.4% and 79.9%, respectively. For voiding symptoms, the correlation coefficient was 0.272, which was higher than that of storage symptoms, SUI and OAB. Conclusions: In cervical cancer patients who have undergone RH, there was a moderate degree of agreement between UDS and symptom questionnaires in evaluating LUTS, but the consistency was poor. Medical personnel should be adequately trained in UDS to ensure LUTS are adequately diagnosed in patients.